Short Communication: Evaluation of a New Rapid Diagnostic Test for Quality Assurance by Kala Azar Elimination Programme in Bangladesh - Md Gulam Musawwir Khan; Mohammad Shafiul Alam; Abu Toha Bhuiyan; Maleka Arjumand Jamil; Bijoy Saha; Mazharul Islam; Rashidul Haque; Moazzem Hossain; Kazi M. Jamil (Journal of Parasitology Research)
In Bangladesh, serological tests have been widely used for the primary screening of visceral leishmaniasis (VL). Several serologic tests are available for the diagnosis of VL. Selection of the best test is important to permit diagnostic differentiation between symptomatic and asymptomatic patients and to reduce cross-reactivity. We evaluated the effectiveness of a new serological test “Onsite Leishmania Ab Rapid Test” as a part of “quality assurance” activities for the kala azar elimination programme of the Government of Bangladesh. Plasma samples of 100 parasitologically confirmed cases of VL along with 101 healthy controls were tested, and “Onsite Leishmania Ab Rapid Test” strip tests were positive in 94 out of 100 confirmed VL cases, whereas four out of 51 healthy subjects from the VL endemic areas also tested positive. All the 50 healthy volunteers tested negative. Thus, the sensitivity and specificity of “Onsite Leishmania Ab Rapid Test” strip test were found to be 94% (95% CI: 87–98) and 96% (95% CI: 90–99), respectively. This study showed that the performance of the “Onsite Leishmania Ab Rapid Test” strip tests was up to the recommended level.